PENGARUH CORPORATE ENVIRONMENTAL PERFORMANCE DAN CORPORATE SOCIAL ACCOUNTING DISCLOSURE TERHADAP CORPORATE ECONOMIC PERFORMANCE - Eva Wany; Siti Asiah Murni; Kholidiah , (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
This research is aimed to recognize the effect of environmental performance and environmental disclosure to Economic Value Added as economic performance measurement by using some variables control such as, profit margin, ownership, environmental concern, and market performance. The type of research done is the type of research by using hypothesis testing which is a research in explaining the relation phenomena between variable. The data used in this research is from the annual financial report and also the continued report of manufactured company listed in BEI and PROPER in 2009-2012 with 17 companies. Analysis hypothesis used in this research is multy linear regression and before doing the test, the classic asumption test of the data has been done. The analysis shows that environmental performance and and socialaccounting disclosure affect to Economic Value Added as the economic performance measurement.From the hypothesis, we can get the result that environmental performance and social accounting disclosure doesn’t give any effect to the economic performance, butThe testing result hypothesis shows that environmental performance and social accounting disclosure jointly effect to the economic performance.